The Treatment of Giant Periurethral Condyloma in Pregnancy Using an Ultrasonic Thermal Scalpel: A Case Report and New Single Session Treatment Option - Ali Yavuzcan; Mete Çağlar; Hakan Turan; Ali Tekin; Seren Topuz; Gizem Yavuzcan; Serdar Dilbaz; Yusuf Üstün; Cihangir Aliağaoğlu; Selahattin Kumru (Case Reports in Obstetrics and Gynecology)
Multiple large polypoid lesions with exophytic appearance occurring in anal and perineal region as a result of human papilloma virus (HPV) infection are referred to as giant condyloma acuminatum (GCA). The conventional treatment of these lesions involves the use of surgical excision, laser, electrocautery, and/or application of trichloroacetic acid. A 28-year-old primigravid patient at 22 weeks of pregnancy presented to the hospital complaining of vaginal bleeding and palpable mass in the vulva. The physical examination revealed a 60 × 35 mm broad-based, fragile, and patchy hemorrhagic polypoid lesion originating 1 cm below the clitoris and completely occupying urethral orifice and partially occluding vaginal vestibule. The patient underwent excision of GCA in the midtrimester using an ultrasonic thermal scalpel (Harmonic Scalpel) without any additional treatment and subsequently delivered a single live healthy baby. The excision of GCA occurring during pregnancy using Harmonic Scalpel can be regarded as a new successful method. Prospective, randomized, and controlled studies are warranted in order to provide clear evidence of the efficiency and safety of HS in the treatment of GCA.